Endovascular Treatment of Intracranial Aneurysms Using the Novel Low Profile Visualized Intraluminal Support EVO Stent: Multicenter Early Feasibility Experience - Michelle Foo; Julian Maingard; Jonathan Hall; Yifan Ren; Goran Mitreski; Lee-Anne Slater; Ronil Chandra; Winston Chong; Ashu Jhamb; Jeremy Russell; Hong Kuan Kok; Mark Brooks; et al. (Neurointervention, 2021)
Purpose Low-profile, self-expandable stents have broadened therapeutic options available for definitive treatment of intracranial aneurysms. The novel Low-Profile Visualized Intraluminal Support (LVIS) EVO stent extends upon the success of its predecessor, the LVIS Jr stent, aiming to enable higher visibility and greater opening ability within a self-expandable and fully retrievable microstent system. In this study, we aim to report the early safety and feasibility experience with the LVIS EVO stent. Materials and Methods A multicenter, retrospective, observational study was conducted on patients who had intracranial aneurysms treated with the LVIS EVO stent across 3 Australian neurovascular centers between February 2020 and September 2020. Short-term technical and clinical outcomes were evaluated. Results A total of 22 LVIS EVO stents were successfully implanted to treat 15 aneurysms (3 ruptured, 12 unruptured) in 15 patients. Aneurysms ranged from 2 mm to 35 mm in dome height. The LVIS EVO stent was used for stent-assisted coiling in 11 patients and flow diversion in 4 patients. There were no device-related procedural complications. There were 2 cases of peri-procedural symptomatic thromboembolic complications and no procedure-related mortality. At early radiological follow up, 10 patients had complete occlusion, 4 patients had small neck remnants, and 1 patient who was managed with flow diversion had a residual aneurysm. Conclusion Early experience with the LVIS EVO stent demonstrated safety and feasibility for stent-assisted coiling as well as flow diversion for intracranial aneurysms. In this heterogeneous cohort, including ruptured, complex, and large aneurysms, all cases were technically successful.